Who Are the People in Your Neighborhood? Personas Populating Unregulated mHealth Research. Issue 1 (March 2020) - Doerr, Megan; Guerrini, Christi
A key feature of unregulated mHealth research is the diversity of participants in this space. Applying an approach drawn from user experience design, we describe a set of archetypal unregulated mHealth researcher "personas, " which range from individuals who seek empowerment or have philanthropic objectives to those who are primarily motivated by financial gain or have misanthropic objectives. These descriptions are useful for evaluating policies applicable to mHealth to understand how they will impact various stakeholders.